2019
DOI: 10.3390/nano9030369
|View full text |Cite
|
Sign up to set email alerts
|

Cell Imaging Using Two-Photon Excited CdS Fluorescent Quantum Dots Working within the Biological Window

Abstract: In recent years, two-photon excited semiconductor quantum dots (QDs) have been the subject of intense investigation due to their long excitation wavelength which helps to achieve deeper penetration and higher image resolution in optical bioimaging. In this paper, water-soluble CdS QDs were synthesized using a hydrothermal method and applied to human liver hepatocellular carcinoma (HepG2) cells. The first-principles calculation suggested that the S-rich defected structure contributes to a narrower band gap comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…This limits the sensitivity of the nanoprobe as the visible photons are prone to scatter in the tissue. Therefore, efforts are made to develop nanoprobe and dyes capable of two-photon excited NIR emission in the region of 650–900 nm. ,, GAGG:CeCr-FA shows the ability of NIR to NIR two-photon excitation together with magneto persistence. Thus, the GAGG:CeCr nanoparticle has excellent potential as a multimodal platform for high contrast and high penetrating in vivo bioimaging.…”
Section: Resultsmentioning
confidence: 99%
“…This limits the sensitivity of the nanoprobe as the visible photons are prone to scatter in the tissue. Therefore, efforts are made to develop nanoprobe and dyes capable of two-photon excited NIR emission in the region of 650–900 nm. ,, GAGG:CeCr-FA shows the ability of NIR to NIR two-photon excitation together with magneto persistence. Thus, the GAGG:CeCr nanoparticle has excellent potential as a multimodal platform for high contrast and high penetrating in vivo bioimaging.…”
Section: Resultsmentioning
confidence: 99%
“…Simultaneous absorption of two photons is of significant interest for a range of applications, particularly imaging, where higher spatial resolution and penetration depth can be achieved through the nonlinear photon-flux dependence of two-photon absorption (2PA) processes. 2PA is particularly useful in biological imaging due to increased transmissivity of biological tissue in the near-IR spectral window, so 2PA improves imaging resolution and penetration depth. 2PA cross sections are measured in units of GM where 1 GM = 1 Göppert Mayer = 10 –50 cm 4 s photon –1 .…”
Section: Steady State Optical Properties Of Cd-chalcogenide Nrs and N...mentioning
confidence: 99%
“…The narrow emission spectrum of QDs make it possible to detect the different sizes of QDs under the same excitation (Kairdolf et al, 2013; Zhang et al, 2003). Therefore, QDs are applied in various application ranging from light‐emitting devices to imaging (Byers & Hitchman, 2011; Jaiswal & Simon, 2004; Onoshima et al, 2015; Zhang et al, 2019; Zvaigzne et al, 2020) and are considered to be potential chemical probes in biological applications. Numerous studies have reported the use of QDs for in vivo imaging of cell membrane, organelles, and receptors (Awasthi et al, 2020; Chan et al, 2002; Le et al, 2020) and for tumor detection (Diagaradjane et al, 2008; Gao et al, 2004; Salama et al, 2020).…”
Section: Introductionmentioning
confidence: 99%